2015
DOI: 10.1037/ppm0000056
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing consensus in a diverse field of scholarly opinions: A comment on Bushman, Gollwitzer, and Cruz (2015).

Abstract: We appreciate the efforts of Bushman, Gollwitzer, and Cruz (2015) to provide new data describing parents' and professionals' opinions regarding effects of media violence. Unfortunately, we feel it is necessary to call attention to apparent errors and inaccuracies in the way those data are interpreted and represented in their article. The article includes flawed analyses, overstates the extent to which there is agreement that media violence has meaningful negative societal effects, and misrepresents the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 32 publications
(63 reference statements)
1
31
2
Order By: Relevance
“…To further add controversy, potential problems with the methodology of Bushman et al and its claims for consensus were also alleged soon after release. In one response article in the same journal, Ivory et al (; see Bushman, Gollwitzer, & Cruz, for reply) expressed the concern that the sampling methods used by Bushman et al were biased, some of the analyses incorrectly done, and the ultimate results ultimately illustrative more of disagreement than consensus. This exchange revealed that scholars were unable to come to a consensus on what was indicative of a consensus.…”
Section: A Brief History Of Video Game Debatesmentioning
confidence: 99%
See 1 more Smart Citation
“…To further add controversy, potential problems with the methodology of Bushman et al and its claims for consensus were also alleged soon after release. In one response article in the same journal, Ivory et al (; see Bushman, Gollwitzer, & Cruz, for reply) expressed the concern that the sampling methods used by Bushman et al were biased, some of the analyses incorrectly done, and the ultimate results ultimately illustrative more of disagreement than consensus. This exchange revealed that scholars were unable to come to a consensus on what was indicative of a consensus.…”
Section: A Brief History Of Video Game Debatesmentioning
confidence: 99%
“…However, controversies over the original Bushman et al (2015) paper emerged earlier when the in press version was released to news media. Two psychological researchers reported that major statistical errors had been found in the manuscript (as reported by Ivory et al, ) during the comment/reply process, and Bushman et al were effectively allowed to mulligan a new set of analyses for the original paper (Etchells & Chambers, ). This raised concerns regarding the transparency of the editorial process for this article.…”
Section: A Brief History Of Video Game Debatesmentioning
confidence: 99%
“…One issue of contention is public resolution statements by professional guilds, such as the APA and AAP, which have linked VVGs to aggression or societal violence. Such statements have been criticized for citation bias issues (failing to acknowledge null studies conflicting with the resolution statements) and for appearing to stack the committees that develop them with known antimedia advocates (Ferguson & Beresin 2017, Hall et al 2011a, Kutner & Olson 2008. This has raised concerns for the integrity of these public statements, whether they misinform the public to promote the guild professions and damage the reputation of science in the process.…”
Section: Professional Guild Resolution Statementsmentioning
confidence: 99%
“…The link between violent video games and violent or aggressive tendencies in real-life has repeatedly been explored over the last two decades, often to entirely contradictory conclusions, and with no clear support (for in-depth summaries of this on-going debate, see [27,34,43,50]). Leading proponents of causal links between violent video games and violent behaviour such as Bushman et al [14] have been accused of manufacturing consensus [37] and sensationalism [49]. Markey and Ferguson called these efforts "The Grand Theft Fallacy" [39], and it has been noted that "scholarly opinions on video games may resemble moral panics" [26].…”
Section: Related Research and Context Violence In Video Gamesmentioning
confidence: 99%